Cannabis use is associated with prevalent coronary artery disease. (14th October 2021) - Skipina, T M S; Patel, N P; Upadhya, B U; Soliman, E Z S
Abstract: Background: Cannabis is the most commonly used illicit drug in the United States and has been associated with an increased risk of acute coronary syndrome (ACS) in multiple observational studies. Purpose: The association of cannabis use with prevalent coronary artery disease (CAD) remains unclear. We hypothesized that cannabis use would also be associated with prevalent CAD among a nationally representative sample of patients. Methods: This analysis included 12, 543 participants (age 39.3±11.6 years, 48.8% male, 35.3% Caucasians) from the National Health and Nutrition Examination Survey years 2011–2018. Cannabis use was defined by self-report. Prevalent CAD was defined by physician diagnosis. Multivariable logistic regression was used to examine the association between cannabis use and prevalent CAD. The consistency of this association was tested among subgroups stratified by race, gender, tobacco smoking status, and comorbidities. Results: In this analysis, 53.1% (n=6, 650) of participants were ever-cannabis users and 1.1% (n=137) had prevalent CAD. After adjusting for covariates, ever-cannabis users had a 90% increased odds of prevalent CAD compared to never users (p=0.003). Those who had used cannabis at least once per month for at least one year had a 68% increased odds of prevalent CAD (p<0.001). Current cannabis users had a near two-fold increased odds of prevalent CAD [OR (95% CI): 1.98 (1.11 – 3.54), p=0.02]. Similar results were seen with heavy cannabis users [OR (95% CI): 1.99 (1.02 – 3.89), p=0.045]. Multiplicative interaction yielded consistent results among the subgroups analyzed. Conclusion: Cannabis use is associated with prevalent CAD. This association remains consistent after adjusting for traditional cardiovascular disease risk factors. This is a novel finding that underscores the potential harmful effects of cannabis use on cardiovascular health and highlights the need for further controlled studies as the drug becomes more accepted by the general population. Funding Acknowledgement: Type of funding sources: None.